Current knowledge on earthworm richness and distribution in Santa Fe province, Argentina - Masin, Carolina Elisabet (2018)
Updated list of earthworms (Oligochaeta: Lumbricina) from Santa Fe (Argentina) is presented in this work, including current data of species richness and territorial distribution status and information collected by Ljungström and collaborators 40 years ago. Field samplings were conducted between 2012 and 2015 in 23 sites, located in 11 of the 19 districts of the province. Earthworms were collected following a standard methodology (Tropical Soil Biology and Fertility). The conservation of specimens was done with 4% formalin solution and their identification was performed according to taxonomy keys. A total of 15 earthworm species were identified and grouped into ten genus and five families: Acanthodrilidae (Dichogaster bolaui, Microscolex dubius), Glossoscolecidae (Glossodrilus parecis), Lumbricidae (Aporrectodea caliginosa, Aporrectodea rosea, Aporrectodea trapezoides, Bimastos parvus, Eisenia fetida, Octolasion tyrtaeum), Megascolecidae (Amynthas gracilis, Amynthas morrisi, Metaphire californica), Ocnerodrilidae (Eukerria saltensis, Eukerria rosea, Eukerria stagnalis). From all the species found five, G. parecis, E. saltensis, E. rosea, E. stagnalis and M. dubius, are native to South America, and the rest were introduced from Asia and Europe. Endogeic species were present in all environments surveyed. In particular, the species exotic A. trapezoides and A. morrisi showed wide geographical distribution, being in at 70 and 50% respectively of total studied sites. One species, E. rosea, which is in the list, was not recorded in the sampling of 40 years ago. The results reveal that remarkable change of biodiversity landscape in this province, associated with soil use and management of productive systems developed over 40 years, could have influenced the distribution and less register of earthworm species.